3D stem cell-laden artificial endometrium: successful endometrial regeneration and pregnancy. (16th August 2021) - Park, Se-Ra; Kim, Soo-Rim; Im, Jae Been; Park, Chan Hum; Lee, Hwa-Yong; Hong, In-Sun
Abstract: Thin endometrium lining or severe endometrial injury which may occur during artificial abortion can cause defective endometrial receptivity and subsequent infertility. Therefore, much effort has been devoted toward regenerating thin or damaged endometrial lining by applying multiple types of stem cells. Even though there are some positive preliminary outcomes, repairing the injured endometrium with stem cells is considerably challenging, due to the lack of an adequate microenvironment for the administrated stem cells within the tissues and subsequent poor therapeutic efficiency. In this context, as an alternative, we fabricated a 3D stem cell-laden artificial endometrium by incorporating several biodegradable biomaterials (collagen and hyaluronic acid) and multiple cellular components of endometrium (endometrial stem cells, stromal cells, and vessel cells) to properly recapitulate the multicellular microenvironment and multilayered structure. Agarose was used as an inert filler substrate to enhance the mechanical integrity of the three-layered artificial endometrium. Various mechanical characteristics, such as morphology, compression properties, swelling, and viscosity, have been evaluated. Various biological features, such as steroid hormone responsiveness, specific endometrial cell-surface marker expressions, and the secretion of multiple growth factors and steroid hormones, as well as the viability of encapsulated endometrial cells are relatively well maintained within the artificial endometrium. More importantly, severe tissue injuries were significantly relieved by transplanting our 3D artificial endometrium into endometrial ablation mice. Remarkably, artificial endometrium transplantation resulted in a successful pregnancy with subsequent live birth without any morphological or chromosomal abnormalities.